Content Analysis of News Reports on Al Jazeera Website Representing Iraqi Archaeological Heritage Under Threat: An Analytical Study during the Period 2019–2024 - Al-Sultani, Hussein Murad Kadhim; Alkufi, Muhannad Abbas Kadhim (ALBAHITH ALALAMI, 2025)
Objectives: The study aims to achieve a set of objectives, most notably: identifying the key issues related to Iraqi archaeological heritage under threat covered by the website during the specified period and revealing the narrative frames and symbolic meanings employed in reporting these issues. This is pursued by answering the main research question: What is the content of news reports representing Iraqi archaeological heritage under threat on Al Jazeera website during the 2019–2024 period?Methodology: The researcher adopted the media survey methodology, using content analysis as a tool for a sample comprising reports published on the Al Jazeera website during the period subject of study.Results: The findings revealed that the reports often highlighted significant concern for threatened or looted archaeological sites, such as the Baghdad Museum, the city of Lagash (Telul al-Habaa), and several sites in Mosul and Dhi Qar. The results also showed that the dominant media discourse relied on narrative framing that portrayed heritage as a victim of conflicts and wars, documenting both the human and material losses resulting from the destruction of cultural legacy. Some reports also emphasized the efforts made to recover stolen artifacts, highlighting the role of Iraqi government bodies and several specialists, such as Wafaa Hassan.Conclusion: The study indicates that Al Jazeera’s media coverage focused on portraying Iraqi archaeological heritage as a civilizational component threatened with extinction due to conflicts, while also highlighting both official and individual efforts to protect and restore it. This reflects the role of media in shaping collective awareness of the value of heritage as part of national identity and human memory.